FUTURISTIC SCOPE OF STEM CELLS IN MEDICINE - P, Sharma; P, Kumar; R, Sharma; Ps, Dhot (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The most potential application of the stem cells (SCs) in human beings lies in their ability to regenerate cells and tissues. They differentiate themselves into specific cell type, thereby availing remarkable source of replacement cells and tissues. They differentiate themselves into specific cell types, thereby availing renewable source of replacement cells and tissues. Their potential of regeneration has now opened many avenues in the field of medical science and research. As a therapeutic adjuvant in near future, the SCs will emerge as an efficient technique to completely heal a number of diseases including diabetes, heart diseases and strokes, osteoarthritis, rheumatoid arthritis, and macular degeneration. The researches, which are underway, some of them will surely be proved as safe and effective SC treatment in the market in due course of time. Keywords: Stem cells, Medicine, Embryonic cells, Heart disease.